Antioxidant activity of thymus citriodorus - Pereira, Olívia R. (2011)
Background and aims: Thymus citriodorus, or lemon thyme, is used as a medicinal plant in the treatment of asthma and other respiratory diseases, although the mechanism of its beneficial properties is poorly understood. The aim of the present study was to determine the antioxidant ability of the polyphenols present in this plant. Methods: An ethanolic extract was prepared and its antioxidant activity was determined by in vitro measurement of its 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging potential, reducing power, and protective effects against the generation of reactive oxygen species (ROS) induced by potassium dichromate (5 and 25 μM) in hepatoblastoma HepG2 cells. The non-toxic range of extract concentrations was determined by MTT test, after exposure of HepG2 cells to the extract (1–200 µg/mL) for 72 h. ROS generation was measured by flow cytometry using dichlorofluorescein diacetate after 48 h of incubation with the extract. Results and discussion: Concentrations of extract able to decrease to 50% (EC50) DPPH absorbance and reducing power were 0.32±0.05 mg/mL and 0.77±0.15 mg/mL, respectively. These findings indicate that the components of the extract have a relevant radical scavenging ability towards nitrogen free radicals and high reducing capacity. As revealed the MTT test, maximal non-toxic concentration of the extract was 50 µg/mL. This concentration was further used to treat HepG2 cells resulting in a decreased rate of ROS production, both under basal conditions or when oxidative stress was induced by potassium dichromate. Antioxidant protection was approximately 60%. Conclusion: Our results suggest that, since luteolin-7-O-glucoside, apigenin-7-O-glucuronide and rosmarinic acid are major components of Thymus citriodorus ethanolic extract [1], these phenolic constituents may be involved in its antioxidant properties. Accordingly, further investigations to elucidate the actual contribution of each compound to the overall protective effect are needed.